2020
DOI: 10.2106/jbjs.19.01170
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Tillaux and Triplane Fractures with 2 to 5 Millimeters of Intra-Articular Gap

Abstract: Background: The treatment of transitional ankle fractures (Tillaux and triplane) is often dictated by the amount of displacement at the articular surface. Although >2 mm is a common indication for operative management, this practice has not been strongly supported by either the pediatric or adult literature. The purpose of this study was to determine whether operative treatment of transitional fractures with 2 to 5 mm of intra-articular gap leads to superior functional outcomes compared with cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…In a retrospective study in 2020, Lurie et al reported that functional results were similar to surgical treatment when the intra-articular gap did not exceed 2.5 mm. The researchers concluded that surgery should be the treatment option for displacements exceeding 2.5 mm [ 3 ]. Computed tomography is required to make this precise measurement and identify the displacement in the joint and physis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study in 2020, Lurie et al reported that functional results were similar to surgical treatment when the intra-articular gap did not exceed 2.5 mm. The researchers concluded that surgery should be the treatment option for displacements exceeding 2.5 mm [ 3 ]. Computed tomography is required to make this precise measurement and identify the displacement in the joint and physis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct radiographs, CT scans, clinical notes, and technical data (open reduction + internal fixation and closed reduction + plastering) and complications (loss of reduction, malunion, implant failure, additional procedure, deep or superficial infection, revision surgery, and leg length discrepancy due to premature physis closure) were recorded. A discrepancy of > 1 cm on radiography and tape measurement was defined as a leg length discrepancy (LLD), while a deformity of > 5 ° on anteroposterior and lateral radiographs was defined as angular deformity [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Non-weight bearing for a period of 4 weeks post-fixation followed by gradual weight bearing is the recommended post-operative protocol. The outcomes of surgical fixation are very good and there is no risk of growth arrest as the child is usually closer to skeletal maturity [39][40][41].…”
Section: Tillaux Fracturementioning
confidence: 99%
“…All fractures with articular displacement > 2 mm are considered as displaced fractures and warrants perfect anatomical reduction and fixation [37,40,49]. Ertl et al in their series had reported poor functional outcomes in the long-term when the residual gap was more than 2 mm.…”
Section: Triplane Fracturesmentioning
confidence: 99%
See 1 more Smart Citation